Populism, Polarization, and the Crises of Democracy - Pally, Marcia (Concilium, 2026)
This article sketches out key features of right-wing populism, especially its reliance on a polarized, us-them worldview - as a response to crises in democracies. It begins with a minimal definition of right-wing populism, those features that allow us to say that a phenomenon is indeed populist. The article then discusses the societal conditions that prod populist responses and how this response works: what societal resources it recruits for legitimation and the socio-political goals that it seeks to achieve. It looks also at important outcomes of populist worldviews/activities on civil society and governance. Christian right-wing populism in the US serves as a case study.